Involvement of 3-methyladenine DNA glycosylases Mag1p and Mag2p in base excision repair of methyl methanesulfonate-damaged DNA in the fission yeast Schizosaccharomyces pombe - Kyoichiro Kanamitsu; Haruna Tanihigashi; Yoshie Tanita; Saki Inatani; Shogo Ikeda (Genes & Genetic Systems, 2007)
Schizosaccharomyces pombe has two paralogues of 3-methyladenine DNA glycosylase, Mag1p and Mag2p, which share homology with Escherichia coli AlkA. To clarify the function of these redundant enzymes in base excision repair (BER) of alkylation damage, we performed several genetic analyses. The mag1 and mag2 single mutants as well as the double mutant showed no obvious methyl methanesulfonate (MMS) sensitivity. Deletion of mag1 or mag2 from an nth1 mutant resulted in tolerance to MMS damage, indicating that both enzymes generate AP sites in vivo by removal of methylated bases. A rad16 mutant that is deficient in nucleotide excision repair (NER) exhibited moderate MMS sensitivity. Deletion of mag1 from the rad16 mutant greatly enhanced MMS sensitivity, and the mag2 deletion also weakened the resistance to MMS of the rad16 mutant. A mag1/mag2/rad16 triple mutant was most sensitive to MMS. These results suggest that the NER pathway obscures the mag1 and mag2 functions in MMS resistance and that both paralogues initiate the BER pathway of MMS-induced DNA damage at the same level in NER-deficient cells or that Mag2p tends to make a little lower contribution than Mag1p.